Ecofisiologia e biomarcadores de estresse oxidativo na caracterização do ciclo de vida pós-embrionário de uma espécie de peixe anual neotropical - Castro, Bruna Dutra de (2019)
Freshwater fish are considered one of the most threatened groups in the world, as aquatic ecosystems are currently facing constant interference from anthropic actions, mainly with the intensification of agriculture that has impacted and de-characterized diverse habitats of many species. To conserve biological diversity in these aquatic environments, it is extremely important to obtain information about the species that constitute these habitats. In this way, physiological tools can be used to characterized biological diversity and its ecological implications, and also include organisms responses to environmental changes and stressors. Annual fish are organisms that live in temporary wetlands that dry out seasonally. Due to this, the life cycle is considered short and fast presenting great potential as biological models for several researches, mainly those related to the study of aging. The aim of the present study was to analyze physiological markers related to the redox balance of the annual fish Cynopoecilus fulgens, endemic to southern Brazil, with environmental variables and estimates of the reproductive period. A total of 443 individuals were collected, including juveniles, adults and senile, between June to November 2016, around the Parque Nacional da Lagoa do Peixe, located in the Coastal Plain of Rio Grande do Sul, in three sampling units (P1, P2 and P3). These animals were euthanized in the field and in the laboratory were measured and weighed. After, they were homogenized for the Superoxide Dismutase, Catalase, Glutathione Peroxidase and Glutathione S-transferase assays, and for the determination of the levels of Lipoperoxidation, through TBARS, Carbonylated Proteins and Total Proteins. The results showed that males and females of C. fulgens use different physiological strategies of their redox balance during the life cycle, being influenced by the reproductive period and environmental variables (biotic and abiotic). Among the strategies, females show a great deal of investment in reproduction, especially in the period of sexual maturation and egg production, evidenced by the higher levels of TBARS when compared to males that seem to invest in somatic growth and body mass. In addition, the variables that had the greatest influence on the oxidative balance of these animals were: temperature, abundance of predator, abundance of annual fish Austrolebias minuano and abundance of C. fulgens. Also, the population of each temporary wetland presented different physiological responses to the adaptation to their life cycle, corroborating the influence of an environmental component as a modulator of this cycle. Additionally, it was observed that the animals of the pools P2 and P3 behave in a similar way among each other presented a longer cycle; suggesting that the antioxidant system of these animals presents high efficiency keeping the levels of lipoperoxidation and carbonylated proteins low. Fish of P1 have their shorter post-hatch life cycle possibly due to increased oxidative stress evidenced by increased lipoperoxidation. These results demonstrate that the use of Neotropical annual fish in the research is highly promising, allowing in-depth study on aging and toxicology testing. In addition, they emphasize the importance of developing environmental conservation strategies to preserve the characteristics of temporary wetlands, establishing these animals as sentinel species.